Examining Older Adults' Attitudes and Perceptions of Cancer Screening and Overscreening: A Qualitative Study - Siddhartha Roy; Jennifer L. Moss; Sol M. Rodriguez-Colon; Chan Shen; Joie D. Cooper; Robert P. Lennon; Eugene J. Lengerich; Alan Adelman; William Curry; Mack T. Ruffin (SAGE Publishing, 2020)
Introduction/Objectives: Screening guidelines for breast, cervical, and colorectal cancer (CRC) are less clear for older adults due to the potential harms that may result from screening. Understanding older adults' attitudes and perceptions, especially racial/ethnic minority and underserved adults, of cancer screening can help health care providers determine how best to communicate with older adults about cancer screening and screening cessation. The objective of this study was to determine how older adults primarily from minority/underserved backgrounds perceive cancer screening and overscreening. Methods: Four focus groups (n = 39) were conducted with adults (>=65 years of age) in 3 community settings in south-central Pennsylvania. Two focus groups were conducted in Spanish and translated to English upon transcription. Focus group data was managed and analyzed using QSR NVivo 12. Inductive thematic analysis was used to analyze the data where themes emerged following the coding process. Results: The focus group participants had an average age of 74 years and were primarily female (74%) and Hispanic (69%), with 69% reporting having less than a high school degree. Four key themes were identified from the focus groups: (1) importance of tailored and targeted education/information; (2) impact of physician/patient communication; (3) impact of barriers and facilitators to screening on cancer screening cessation; and (4) awareness of importance of screening. Participants were more likely to be agreeable to screening cessation if they received specific information regarding their health status and previous medical history from their physician as to why screening should be stopped and told by their physician that the screening decision is up to them. Conclusions: Older adults prefer individualized information from their physician in order to justify screening cessation but are against incorporating life expectancy into the discussion. Future research should focus on developing interventions to test the effectiveness of culturally tailored screening cessation messages for older adults.